Judah and the Judeans in the Achaemenid period: negotiating identity in an international context - Lipshits, ʿOded; Knoppers, Gary; Oeming, Manfred (Eisenbrauns, 2011)
Judean identity and ecumenicity : the political theology of the priestly document / Konrad Schmid -- Torah and identity in the Persian period / Joachim Schaper -- The absent presence : cultural responses to Persian presence in the Eastern Mediterranean / Anselm C. Hagedorn -- Ethnicity and identity in Isaiah 56-66 / Christophe Nihan -- Trito-Isaiah's intra- and internationalization : identity markers in the Second Temple period / Jill Middlemas -- From Ezekiel to Ezra-Nehemiah : shifts of group identities within Babylonian exilic ideology / Dalit Rom-Shiloni -- Israel's identity and the threat of the nations in the Persian period / Jakob Wöhrle -- The rite of separation of the foreign wives in Ezra-Nehemiah / Yonina Dor -- The holy seed : the significance of endogamous boundaries and their transgression in Ezra 9-10 / Katherine Southwood -- What do priests and kings have in common? : priestly and royal succession narratives in the Achaemenid Era / Deirdre N. Fulton -- Yahwistic names in light of late Babylonian onomastics / Paul-Alain Beaulieu -- "Judean" : a special status in neo-Babylonian and Achemenid Babylonia? / Laurie E. Pearce -- Some observations on the traditions surrounding "Israel in Egypt" / Donald Redford -- Judean identity in Elephantine : everyday life according to the Ostraca / André Lemaire -- The interaction of Egyptian and Aramaic literature / Joachim Friedrich Quack -- Yehudite identity in Elephantine / Bob Becking -- Judean ambassadors and the making of Jewish identity : the case of Hananiah, Ezra, and Nehemiah / Reinhard G. Kratz -- Negotiating identity in an international context under Achaemenid rule : the indigenous coinages of Persian-period Palestine as an allegory / Oren Tal -- Judaeans, Jews, children of Abraham / Joseph Blenkinsopp -- The controversy about Judean versus Israelite identity and the Persian government : a new interpretation of the Bagoses story (Jewish antiquities XI.297-301) / Rainer Albertz -- Surviving in an imperial context : foreign military service and Judean identity / Jacob L. Wright -- 'el-mĕdînâ ûmĕdînâ kiktābāh : scribes and scripts in Yehud and in Achaemenid transeuphratene / David S. Vanderhooft -- Jewish identity in the Eastern diaspora in light of the book of Tobit / Manfred Oeming -- The identity of the Idumeans based on the archaeological evidence from Maresha / Amos Kloner
"In April, 2008, an international colloquium was held at the University of Heidelberg--the fourth convocation of a group of scholars (with some rotating members) who gathered to discuss the status of Judah and the Judeans in the exilic and postexilic periods. The goal of this gathering was specifically to address the question of national identity in the period when many now believe this very issue was in significant foment and development, the era of the Persian/Achaemenid domination of the ancient Near East"--ECIP summary
Literaturangaben
Keywords: Achaemenid dynasty -- 559-330 B.C -- Congresses; Achämeniden; Bible -- Old Testament -- Criticism, interpretation, etc -- Congresses; Bibel; Bibel -- Altes Testament; Judaea (Region) -- Ethnic relations -- Congresses; Judäa; Konferenzschrift -- 2008 -- Heidelberg; Geschichte 586 v. Chr.-70; Israel